Electrophysiologic vestibular evaluation in type 2 diabetic and prediabetic patients: Air conduction ocular and cervical vestibular evoked myogenic potentials. (August 2015) - Konukseven, Ozlem; Polat, Sefika Burcak; Karahan, Sevilay; Konukseven, Ertan; Ersoy, Reyhan; Cakir, Bekir; Kutluhan, Ahmet; Aksoy, Songul
Abstract Objective: Chronically increased blood glucose levels may affect the vestibular system by damaging cells and neural structures in diabetes mellitus (DM). We aimed to search the effects of neurovascular degeneration on the vestibular system in type 2 DM and prediabetic patients by using air-conducted ocular (oVEMP) and cervical (cVEMP) vestibular evoked myogenic potentials. Design: Prospective study. Study sample: Thirty diabetic, 30 prediabetic patients, and 31 age- and sex-matched controls having no peripheral or central vestibular disease, were enrolled. All participants were evaluated by audiovestibular tests, oVEMP, and cVEMP. Results: In the diabetic group, mean values of both oVEMP and cVEMP p1, n1 latencies were significantly longer compared to the prediabetic group and the control group, whereas latencies were similar in prediabetic and the control groups. Bilateral neural dysfunction was recognized in both tests and lateralization was not seen in VEMP asymmetric ratios. In the diabetic group, prevalence of pathological p1 and n1 latencies in oVEMP were 30.4% and 37.5%, whereas they were 53.7%, 59.3% in cVEMP, respectively. p1 latencies of cVEMP and oVEMP were positively correlated with HbA1c and fasting plasma glucose level in the diabetic group. Conclusion: Subclinical vestibular neuropathy can be a newly defined diabetes-related complication.